IMPLEMENTASI SAK DALAM PENYUSUNAN LAPORAN KEUANGAN TOKO XYZ DI KOTA SERANG - Afriani, Raden Irna; Triana, Leni; Khadijah, Ina; Yuliah, Yuliah (Yayasan Education and Social Center, 2024)
This research aims to explore the implementation of Financial Accounting Standards (SAK) in preparing the financial reports of XYZ Shop in Serang City. Qualitative research methods were used to gain an in-depth understanding of the application of SAK in daily practice. The research results show that Toko However, this shop faces challenges in the form of limited human resources who understand SAK in depth and limited technological infrastructure. Nevertheless, the benefits of implementing SAK are clear, such as increasing the trust of external stakeholders, better strategic decision making, and compliance with tax regulations. This research reveals that implementing SAK is not only a formal requirement but also a valuable investment for business growth and sustainability